The Truth About Opium : Being a Refutation of the Fallacies of the Anti-Opium Society and a Defence of the Indo-China Opium Trade. - Brereton, William H. (The Floating Press, 2014)
Based on a series of talks on the controversial subject of opium use and trafficking, The Truth About Opium asserts that much of the propaganda disseminated in the West about the drug has been exaggerated, and in some instances, entirely false. Brereton draws on his own experiences and observations in China to weave a compelling counterargument.